Revolutionizing Recruitment: Exploring the Ethical, Psychological, and Strategic Dimensions of Artificial Intelligence in Talent Acquisition - Muhammad Nawaz,; Dr. Shahid Ali Durrani,; Javeria Arshad, (Dialogue Social Science Review (DSSR), 2025)
Artificial intelligence or AI has been seen to be having a positive impact in talent acquisition as it brings about efficiency, scalability and decision making. This research explores examples of AI’s ethical, psychological, and strategic aspects in recruitment through a quantitative survey of 300 participants (200 candidates and 100 recruiters) and qualitative data from semi-structured interviews. The results suggest that perceived fairness does have a strong influence on trust in these systems which in turn moderates the connection between fairness and candidate engagement. As with most digital media, efficiency of recruitment is another area where area engagement takes form and shows how AI is not a mere tactical tool. Moderation analysis indicates that organizational culture enhances the positive relationship between trust and engagement and this proves that culture plays a critical role in AI implementation. Qualitative evidence adds to the understanding of the body of knowledge by asserting that meeting such needs requires transparency, Au-efficiency, and strong bias elimination processes. The study, therefore, has implications on proven theories like the TAM and Strategic Alignment Theory and proposes concrete guidelines for fairness, trust and inclusion when addressing recruitment through AI. These studies propose a framework to guide the effective and ethically appropriate implementation of AI in recruitment based on key issues clients and organizations have about this technology.